The role of brain‐derived neurotrophic factor in learned fear processing: an awake rat fMRI study. (5th January 2016) - Harris, A. P.; Lennen, R. J.; Brydges, N. M.; Jansen, M. A.; Pernet, C. R.; Whalley, H. C.; Marshall, I.; Baker, S.; Basso, A. M.; Day, M.; Holmes, M. C.; Hall, J.
Abstract : Brain‐derived neurotrophic factor (BDNF) signaling is implicated in the etiology of many psychiatric disorders associated with altered emotional processing. Altered peripheral (plasma) BDNF levels have been proposed as a biomarker for neuropsychiatric disease risk in humans. However, the relationship between peripheral and central BDNF levels and emotional brain activation is unknown. We used heterozygous BDNF knockdown rats (BDNF +/− ) to examine the effects of genetic variation in the BDNF gene on peripheral and central BDNF levels and emotional brain activation as assessed by awake functional magnetic resonance imaging (fMRI). BDNF +/− and control rats were trained to associate a flashing light (conditioned stimulus; CS) with foot‐shock, and brain activation in response to the CS was measured 24 h later in awake rats using fMRI. Central and peripheral BDNF levels were decreased in BDNF +/− rats compared with control rats. Activation of fear circuitry (amygdala, periaqueductal gray, granular insular) was seen in control animals; however, activation of this circuitry was absent in BDNF +/− animals. Behavioral experiments confirmed impaired conditioned fear responses in BDNF +/− rats, despite intact innate fear responses. These data confirm a positive correlation [ r = 0.86, 95% confidence interval (0.55, 0.96); P = 0.0004] between peripheral and central BDNF levels and indicate a functional relationship between BDNF levels and emotional brain activation as assessed by fMRI. The results demonstrate the use of rodent fMRI as a sensitive tool for measuring brain function in preclinical translational studies using genetically modified rats and support the use of peripheral BDNF as a biomarker of central affective processing. Abstract : BDNF +/− rats exhibit impaired amygdala activation during a learned fear‐associated task using awake functional magnetic resonance imaging.